Procedure for Providing KUR IB Financing and the Strategy for Preventing Problem Financing at Bank Sinarmas Syariah KCS Surabaya - Ilahi, Ina Kurnia; Marsa, Dinda; M., M. Akhmas; Dina, Mutiara (Majapahit Journal of Islamic Finance and Management, 2022)
Financing is a fund distribution activity carried out by banks to customers. This study aims to determine the procedures and systems implemented by Bank Sinarmas Syariah KCS Surabaya in providing KUR IB financing as well as the supervision process carried out as an effort to prevent problematic financing. This study used a descriptive qualitative method. The data used is in the form of primary data from interviews with informant selection using purposive sampling techniques and several supporting documents as secondary data. This research shows that Bank Sinarmas Syariah KCS Surabaya implements a strategy in the form of accurate financing analysis by applying 5C aspects and conducting supervision as a form of risk mitigation. Bank Sinarmas Syariah KCS Surabaya is considered very healthy with an NPF of 0%.